1.3: An Evaluation Method of TFT Integrated Gate Driver for UHD Display. (28th November 2018) - Liao, Congwei; Wang, Ying; Zeng, Limei; Zhou, Yifang; Wang, Tianhong; Lv, Xiaowen; Lin, Lei; Liu, Xiaodi; Jiang, Boren; Chen, Shuzhi; Zhang, Min; Zhang, Shengdong
Abstract : Reliability issues of TFT integrated gate driver are still of great concern for large size (i.e. TV) display applications, especially for a‐Si:H TFT integrated panels with stressing test of high temperature and high humidity (HTHHO). In this paper, current detection method is proposed for gate driver failure identification. Measurements of 55‐inch UHD TV (4K) panel with integrated gate driver are carried out. It is found that gate driver failure after HTHHO are strongly associates with via‐hole open of clock bus‐lines. It is demonstrated that current through clock lines will be increased with prolonged falling edge due to multi‐pulses of gate driver outputs. And clock bus‐line open is caused by oxygen of Cu after long operating time during the stressing test.